Pickering emulsions co-stabilized by composite protein/ polysaccharide particle-particle interfaces: Impact on in vitro gastric stability. (November 2018) - Sarkar, Anwesha; Ademuyiwa, Valerie; Stubley, Samuel; Esa, Nur Hanesa; Goycoolea, Francisco M.; Qin, Xiaofei; Gonzalez, Fernando; Olvera, Clarita
Abstract: The objective of this study was to delay the rate and extent of gastric destabilization of emulsions using composite particle-particle layers at the O/W interface. Pickering emulsions (20 wt% oil) were prepared using lactoferrin nanogel particles (LFN, D h = 100 nm) (1 wt%) or a composite layer of LFN and inulin nanoparticles, latter was enzymatically synthetized by inulosucrase IslA from Leuconostoc citreum (INP) ( D h = 116 ± 1 nm) (1 wt% LFN 3 wt% INP). The hypothesis was that creating a secondary layer of biopolymeric particles might act as a barrier to pepsin to access the underlying proteinaceous particles. Droplet size, microscopy (optical and transmission electron microscopy (TEM)), ζ -potential and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) were used to understand the colloidal fate of these Pickering emulsions in an in vitro gastric model (pH 3, 37 ○ C, pepsin). The ζ -potential measurements and TEM images confirmed that LFN and INP were at the O/W interface, owing to the electrostatic attraction between oppositely charged LFN (+29.3 ± 0.7 mV) and INP (−10 ± 1.8 mV) at both neutral and gastric pH. The SDS-PAGE results revealed that adsorbed LFN was less prone to pepsinolysis as compared to a typical protein monolayer at the interface. Presence of INP further decreased the rate and degree of hydrolysis of the LFN (>65% intact protein remaining after 60 min of digestion) by acting as a steric barrier to the diffusion of pepsin and inhibited droplet coalescence. Thus, composite particle-particle layers (LFN + INP) at droplet surface shows potential for rational designing of gastric-stable food and pharmaceutical applications. Graphical abstract: Image 1 Highlights: Primary Pickering emulsion was prepared using lactoferrin nanogel particles (LFN). Secondary emulsion was prepared by coating with anionic inulin nanoparticles (INP). LFN at oil-water (O/W) interface was prone to gastric digestion by pepsin at pH 3. Presence of INP at O/W interface acted as a steric barrier to proteolysis of LFN. Interfacial particle-particle layers can improve gastric stability of emulsions.